Effect of leakage current and dielectric constant on single and double layer oxides in MOS structure - Laha, Pinaki; Panda, A. B.; Dahiwale, S.; Date, Kalyani S.; Patil, K. R.; Barhai, P. K.; Das, A. K.; Banerjee, Indrani; Mahapatra, S. K. (Thin Solid Films, 2010)
MOS structure of Al/Al2O3/n-Si, Al/TiO2/n-Si and Al/Al2O3/TiO2/n-Si was obtained by deposition of Al2O3 and TiO2 on silicon substrate by RF Magnetron Sputtering system. The total thickness of the oxide layer similar to 40 +/- 5 nm in the MOS structure was kept constant. Samples were characterized by X-Ray diffraction (XRD). X-Ray photoelectron spectroscopy (XPS), Impedance analyzer and Current-voltage (J-V) characteristics. The variations in the dielectric constant and tan 8 of the MOS capacitor in the frequency range of 1000Hz-1MHz were measured by impedance analyzer. The variation in dielectric constant of the Al/Al2O3/TiO2/n-Si multilayer compared to single layer of Al/Al2O3/n-Si and Al/TiO2/n-Si is due to high probability of defects, lattice mismatch and interface interactions. The steep rise of Tan 6 values in the Al/Al2O3/TiO2/n-Si structure is due to the resonance effect of both Al2O3 and TiO2 layers. The leakage current mechanisms of MOS structures were extracted from Schottky coefficient and Poole-Frenkel coefficient. Theoretical values of Schottky coefficients (beta(SC)) and Poole-Frenkel coefficients (beta(PF)) for each sample were estimated using the real part of the dielectric constant. The experimental values were calculated from J-V characteristics and compared with theoretical values. The appropriate model has been proposed. It was found that Schottky and Poole-Frenkel mechanisms are applicable at low and high field respectively for all MOS structures. The combination of Al/Al2O3/TiO2/n-Si is found to be a promising structure with high dielectric constant and low leakage current suitable for MOS devices. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Al2O3; dielectric constant; Leakage current; MOS device; Poole-Frenkel emission; Schottky emission; TiO2

Preparation of Ni3S2 and Ni3S2-Ni nanosheets via solution based processes - Busupalli, Balanagulu; Date, Kalyani S.; Datar, Suwarna; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2015)
An easy and convenient preparation of nanometer-thick sheets of Ni3S2 and Ni3S2–Ni from solution processed molecularly thin sheets of Ni-thiolates is described. Both the Ni3S2 and Ni3S2–Ni possessed sheet-like morphologies and displayed room temperature ferromagnetic characteristics. The ferromagnetic nature of these samples was also confirmed by MFM studies, and AFM/TEM investigations substantiated the sheet-like morphology of the samples.

Attempt to correlate surface physics and chemical properties : molecular beam and Kelvin probe investigations of Ce 1-x Zr x O 2 thin films - Kolekar, Sadhu K.; Dubey, Anjani; Date, Kalyani S.; Datar, Suwarna; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2016)
What is the correlation between physical properties of the surfaces (such as surface potential, electronic nature of the surface), and chemical and catalysis properties (such as chemisorption, sticking probability of surface)? An attempt has been made to explore any correlation that might exist between the physical and chemical properties of thin film surfaces. Kelvin probe microscopy (KPM) and the molecular beam (MB) methods were employed to carry out the surface potential, and oxygen adsorption and oxygen storage capacity (OSC) measurements on Ce1−xZrxO2 thin films. A sol–gel synthesis procedure and spin-coating deposition method have been applied to make continuous nanocrystalline Ce1−xZrxO2 (x = 0–1) (CZ) thin films with uniform thickness (35–50 nm); however, surface roughness and porosity inherently changes with CZ composition. MB studies of O2 adsorption on CZ reveal high OSC for Ce0.9Zr0.1O2, which also exhibits highly porous and significantly rough surface characteristics. The surface potential observed from KPM studies varied between 30 and 80 mV, with Ce-rich compositions exhibiting the highest surface potential. Surface potential shows large changes after reduction or oxidation of the CZ film demonstrating the influence of Ce3+/Ce4+ on surface potential, which is also a key to catalytic activity for ceria-based catalysts. The surface potential measured from KPM and the OSC measured from MB vary linearly and they depend on the Ce3+/Ce4+ ratio. More and detailed studies are suggested to arrive at a correlation between the physical and chemical properties of the surfaces.